Writing the (researcher) self: reflective practice and undergraduate research. Issue 3 (3rd May 2016) - Nye, Adele; Clark, Jennifer; Bidwell, Pam; Deschamps, Briahannon; Frickman, Lisa; Green, Jennifer
Abstract: This paper discusses the way in which postmodern emergence was used to assist a group of undergraduate students come to new understandings of research practice as they participated in a reflective component of an Undergraduate Research Summer School. Students were encouraged to 'write the (researcher) self' through a collaborative writing group based on the theoretical and pedagogical work of Somerville. Postmodern emergence highlights three stages of learning; firstly, assigning time for wondering, then a liminal space for becoming and finally an opportunity for generating new knowledge. This article is both the tangible product of this emergence reflective writing process and a recommendation about the capacity of undergraduate students to engage with their own professionalisa tion and meaning- making.